2023
DOI: 10.2147/opth.s402082
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Annual Vision Screening in Diabetic Adults: Analysis of the 2019 National Health Interview Survey

Abstract: Purpose To determine the association(s) between receiving an annual eye exam and various economic, social, and geographic factors assessed in the 2019 National Health Interview Survey (NHIS) among adults with diabetes. Patients and Methods Data from adults 18 years of age and older relevant to self-reported non-gestational diabetes diagnosis and eye exam within the last 12 months were extracted from the 2019 NHIS dataset. A multivariate logistic regression model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Our findings regarding the association of socioeconomic factors with DR screening are consistent with prior studies . Low socioeconomic status was revealed to be associated with DR screening nonadherence, with studies showing that financial barriers or lack of health insurance were associated with not having an eye examination within 12 months for adults with diabetes .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings regarding the association of socioeconomic factors with DR screening are consistent with prior studies . Low socioeconomic status was revealed to be associated with DR screening nonadherence, with studies showing that financial barriers or lack of health insurance were associated with not having an eye examination within 12 months for adults with diabetes .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our study showed that participants with food or housing instability had lower odds of having visited an eye care practitioner in the past year, reinforcing prior studies demonstrating that financial instability, such as food instability and housing instability, and paying bills were associated with not receiving eye care . Low educational level was also shown to be associated with nonadherence to DR screening recommendations in previous studies, likely due to limited health literacy . We also found that participants with a college or advanced degree were more likely to have visited an eye care practitioner in the past year.…”
Section: Discussionmentioning
confidence: 99%